2014
DOI: 10.1016/j.ecoleng.2014.05.009
|View full text |Cite
|
Sign up to set email alerts
|

An approach to the metabolic degradation of diethylketone (DEK) by Streptococcus equisimilis: Effect of DEK on the growth, biodegradation kinetics and efficiency

Abstract: The degradation of diethylketone by Streptococcus equisimilis was evaluated. The toxicity of diethylketone was assessed evaluating the growth of the bacteria for the range of diethylketone concentration between 0 and 6.4 g L −1. The maximum specific growth rate achieved is 0.555 h −1 at 3.2 g L −1 of initial diethylketone concentration, followed by a slight decrease, suggesting that higher concentrations of diethylketone negatively affect the growth. The biodegradation efficiency (%) obtained was approximately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…A blank, containing culture medium and bacteria was used to assess the standard growth of Streptococcus equisimilis. The toxicity of DEK towards S. equisimilis was reported by Costa et al (2014).…”
Section: Effect Of the Initial Metal Concentration On Microbial Growthmentioning
confidence: 97%
See 1 more Smart Citation
“…A blank, containing culture medium and bacteria was used to assess the standard growth of Streptococcus equisimilis. The toxicity of DEK towards S. equisimilis was reported by Costa et al (2014).…”
Section: Effect Of the Initial Metal Concentration On Microbial Growthmentioning
confidence: 97%
“…Since Ni(II) starts to precipitate in the form of Ni(OH) 2 at pH of 7.6, it is concluded that the decrease of Ni(II) concentration occurs by biological processes such as biosorption (Espinozo et al, 2012). These processes result from chemical bonds formed between the ion metal and functional groups present on the bacteria surface (phosphate, carbohydrate, amide I and amide II) (Costa et al, 2014).…”
Section: Effect Of Metal On the Microbial Growthmentioning
confidence: 99%
“…DEK's toxicity towards Penicillium sp., Alternaria sp. and Streptococcus equisimilis is reported in Costa et al (2014Costa et al ( , 2015.…”
Section: Introductionmentioning
confidence: 99%
“…The increased use of organic compounds in almost, if not all, industrial sectors as well as in household activities and consequent discharge and accumulation into the environment has increased in an extremely significant way in the past years [2,[12][13][14]. Most of these compounds are extremely toxic to humans due to (i) their general carcinogenic and mutagenic properties, (ii) their capacity to form intermediates with the same or even the higher level of toxicity [15] and (iii) their persistence and mobility into the different environmental matrices [7].…”
Section: Introductionmentioning
confidence: 99%